Web content management with documentum : - Kathuria, Gaurav (Packt, 2006)
One of the world leaders in Enterprise Content Management, the EMC Documentum family of applications helps you manage all types of content across multiple departments within a single repository. With the Web Content Management suite of applications, you can efficiently manage content and underlying processes for your Web properties, and ensures that they are responsive to business needs. To fully realize the power of this system can seem daunting, but this book will help you achieve that. With easy to follow examples, this book will take you the simplest and most straightforward route to success. Along the way, you will learn insights that only a seasoned professional would know. Packed with practical examples, you will get hands-on with the powerful features of Documentum to grow your skills and confidence. You will see tips and tricks to handle complexities of the system, and avoid the common errors that waste your time. From installing and getting started with Documentum, you will see how to design and develop Documentum applications, before rounding off with deployment.